Properties of 0.94Bi0.5Na0.5TiO3-0. 06BiAlO3ceramics prepared by two steps sintering technique - Supalak Manotham (2018)
In this research, 0.94Bi0.5Na0.5TiO3-0.06BiAlO3ceramics were prepared by the conventional solid-state reaction and the two steps sintering. X-ray diffraction analysis revealed that both samples showed a pure perovskite phase. Scanning electron microscopy study revealed that both ceramics had similar microstructure. The two steps sintering affects the phase transition temperature of the ceramics. Dielectric and ferroelectric properties of the two steps sintering samples are better than that of the conventional sample. The results were related to the densification and the degree of crystallinity of the samples. © 2014 Copyright Taylor and Francis Group, LLC.